N95 vs Half-face Respirator Wear in Surgical Trainees: Physiologic and Psychological Effects of Prolonged Use. Issue 4 (December 2021) - Cohen, Erin R.; Peña, Stefanie; Misztal, Carly; Iglesias, Thomas; Alejandro, Mantero; Dinh, Christine T.; Holt, Gregory; Thomas, Giovana R.
Objectives: As specialists of the upper airway, otolaryngologists are at high risk for COVID-19 transmission. N95 and half-face respirator (HFR) masks are commonly worn, each with advantages in functionality and comfort. In this study, physiologic and psychological parameters of prolonged N95 vs HFR wear were compared. Study Design: Prospective crossover cohort study. Setting: Single academic tertiary care hospital. Methods: A prospective crossover cohort study was performed. Healthy otolaryngology trainees and medical students (N = 23) participated and wore N95 and HFR masks continuously for 3 hours each on separate days. Various measures were analyzed: vitals, spirometry variables, scores on the State-Trait Anxiety Inventory and HIT-6 (Headache Impact Test–6), distress, and "difficulty being understood." Results: The average age was 26.3 years (SD, 3.42). There were no significant differences in vital signs and spirometry variables between N95 and HFR wear. N95 wear was associated with decreases in oxygen saturation of approximately 1.09% more than with HFRs (95% CI, 0.105-2.077). State-Trait Anxiety Inventory scores increased more with HFR wear when compared with mean changes with N95 wear (95% CI, 1.350-8.741). There were no significant differences in HIT-6 scores or distress levels between masks. The proportions of participants reporting difficulty being understood was significantly higher with HFRs. Conclusions: Oxygen saturation decreases with prolonged N95 wear, but anxiety and difficulty being understood are greater with HFR wear. Although HFRs have less resistance to gas exchange, N95 respirators may produce less anxiety and distress in clinical situations. Further studies are warranted to evaluate the clinical significance of these differences. Level of Evidence: 2.